2015
DOI: 10.1038/nprot.2015.049
|View full text |Cite|
|
Sign up to set email alerts
|

Cobalt-based nanocatalysts for green oxidation and hydrogenation processes

Abstract: This protocol describes the preparation of cobalt-based nanocatalysts and their applications in environmentally benign redox processes for fine chemical synthesis. The catalytically active material consists of nanoscale Co3O4 particles surrounded by nitrogen-doped graphene layers (NGrs), which have been prepared by pyrolysis of phenanthroline-ligated cobalt acetate on carbon. The resulting materials have been found to be excellent catalysts for the activation of both molecular oxygen and hydrogen; in all teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(68 citation statements)
references
References 22 publications
1
65
0
2
Order By: Relevance
“…Beller et al. suggested that metal oxide nanoparticles catalyze the oxidation of the −OH group to the corresponding −CHO with K 2 CO 3 as the additive for expediting the hydrogen abstraction . Conversely, CoO x ‐N/C here achieved excellent performance in neutral medium.…”
Section: Methodsmentioning
confidence: 95%
“…Beller et al. suggested that metal oxide nanoparticles catalyze the oxidation of the −OH group to the corresponding −CHO with K 2 CO 3 as the additive for expediting the hydrogen abstraction . Conversely, CoO x ‐N/C here achieved excellent performance in neutral medium.…”
Section: Methodsmentioning
confidence: 95%
“…Recently, non‐noble‐metal nanoparticles supported on nitrogen‐doped carbon have attracted attention as substitutes for noble‐metal catalysts in various redox reactions . Particularly, Beller and coworkers have developed heterogeneous cobalt catalysts by simple pyrolysis of Co complexes with nitrogen‐containing ligands on carbon supports . These catalysts have shown high activity and selectivity for several applications such as hydrogenation of nitroarenes, oxidative esterification, and recently dehydrogenation of formic acid .…”
Section: Figurementioning
confidence: 99%
“…The procedure was adapted from that reported for the synthesis of Co/Phen based catalysts [58]. Cobalt(II) acetate tetrahydrate was added to absolute ethanol (40 mL of EtOH for 1 mmol of Co(OAc)2·4H2O) and stirred until complete solubilization (10 min., formation of a clear purple solution).…”
Section: Catalysts Preparationmentioning
confidence: 99%
“…Hence, merging rationally-designed suitable modified supports with cheap transition metals permits access to the design of active, selective and cheap catalytic materials thus allowing to match or to outperform noble-metal-based catalysts. During the last three years, some of us reported the preparation of active and selective NGr-decorated Co-based catalysts from the pyrolysis of in situ generated 1,10-phenanthroline (Phen) metal complexes using Vulcan® XC 72 R carbon [52][53][54][55][56][57][58][59][60], ceria [61] or α-alumina as supports [62]. Some of the obtained nanoscale catalysts exhibit a core-shell architecture in which a Co metallic core is enveloped by an oxidic sheath composed of Co3O4.…”
Section: Introductionmentioning
confidence: 99%